Does extended experience with other-race nannies predict racial bias in the preschool years? - Setoh, Peipei (2023)
Most existing studies on racial bias reduction have used short-term interracial interaction interventions with fleeting effects. The current natural experiment examined whether daily interactions with other-race nannies relate to reduced racial bias in the preschool years. We capitalized on a unique child-rearing situation in Singapore whereby children are often cared for by other-race nannies since infancy. Singaporean Chinese 3- to 6-year-olds (N = 100) completed explicit and implicit racial bias measures assessing their preferential bias favoring own-race adults over adults of their nannies' race. Differential findings were obtained for children's explicit and implicit racial bias. Extensiveness, but not mere presence, of other-race nanny experience was associated with lower levels of explicit racial bias in children. In contrast, neither presence nor extensiveness of other-race nanny experience was associated with children's implicit racial bias. Together, these findings suggest that long-term and extensive contact with an other-race caregiver could have subtle mitigating effects on children's explicit, but not implicit, racial bias.